2018
DOI: 10.1021/acsnano.8b00776
|View full text |Cite
|
Sign up to set email alerts
|

Expansion Stimulated Emission Depletion Microscopy (ExSTED)

Abstract: Stimulated emission depletion (STED) microscopy is routinely used to resolve the ultrastructure of cells with a ∼10-fold higher resolution compared to diffraction limited imaging. While STED microscopy is based on preparing the excited state of fluorescent probes with light, the recently developed expansion microscopy (ExM) provides subdiffraction resolution by physically enlarging the sample before microscopy. The expansion of the fixed cells by cross-linking and swelling of hydrogels easily enlarges the samp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(156 citation statements)
references
References 41 publications
3
153
0
Order By: Relevance
“…To further enhance the resolution, ExM has been combined with structured illumination microscopy (SIM) 13,14 and stimulated emission depletion (STED) microscopy 2,15 . By careful optimization of the expansion protocol U-ExM demonstrated that even ultrastructural details of multiprotein complexes such as centrioles can be truthfully preserved 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To further enhance the resolution, ExM has been combined with structured illumination microscopy (SIM) 13,14 and stimulated emission depletion (STED) microscopy 2,15 . By careful optimization of the expansion protocol U-ExM demonstrated that even ultrastructural details of multiprotein complexes such as centrioles can be truthfully preserved 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In principle, super‐resolution instruments can be used with ExM samples to harness the advantages of both methods. Structured illumination microscopy (SIM), for example, was applied to expanded samples to achieve resolutions comparable with those of SMLM, whereas STED combined with ExM (ExSTED) produced a resolution of 10 nm . However, ExSTED cannot utilize the highest STED resolution because photobleaching prevents the use of the maximum depletion intensity.…”
Section: Methodsmentioning
confidence: 99%
“…CRL-1651) that are easy to culture and grow rapidly (Gluzman, 1981), but other mammalian cell lines are also typically used such as U2OS , BS-C-1 (Bates et al, 2007;Lin et al, 2018), or HeLa, which are thicker and can be more challenging to image (Gao et al, 2018). It is important to know a bit about the underlying biology of the chosen cell line (use as a biological model, tumor origin…) in order to understand the possible singularities in their organization.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Moreover, higher labeling density for a given structure can be obtained by using several antibodies against different epitopes within this structure. This strategy has been used to maximize signal for synapses (Sigal et al, 2015) and microtubules in SMLM or Expansion Microscopy (Gao et al, 2018). Similarly, we usually label microtubules with a combination of anti-αand anti-ß-tubulin monoclonal antibodies to obtain a dense labeling in STORM and PAINT ( Fig.…”
Section: Blocking and Primary Antibodies Incubationmentioning
confidence: 99%